TINJAUAN PELAKSANAAN PROGRAM PENGEMBANGAN UKM GO ONLINE PADA KOMUNITAS SHOPEE SAMARINDA TAHUN 2019 - Zulkifli Zulkifli; Abdul Rachim Rachim (LPPM Universitas Malikussaleh – Indonesia, 2020)
Utilization of information technology raises a slight difference in cost but will provide significant added value or return. Business management with the help of information technology will produce efficiency and effectiveness both in relation to the production / service process and marketing. The ability of MSMEs in providing information technology facilities can still be suppressed, for example by utilizing free software that is easy to download on the internet.Referring to research problems and research objectives that will provide an understanding and describe the implementation of the implementation of the SME Go Online development program in the Shopee Samarinda community in 2019, this research uses a qualitative approach.There are two shopee samarinda activities that are routinely carried out including Ngupee or gathering shopee sellers, the second is SME development.The Ngupee event itself was formed by Shopee as a meeting place for Shopee with sellers throughout Indonesia as well as sharing knowledge to increase sales at Shopee. Meanwhile, MSME coaching, which is inviting MSMEs to realiz. Pendahuluan 1.1.Latar Belakang Berdasarkan data Kementerian Koperasi dan UKM (Kemenkop UKM) dari total 64,19 juta pelaku UMKM di Tanah Air, baru 13 persen yang terhubung dengan pasar daring atau marketplace. Dalam upaya pembangunan perekonomian nasional, meningkatkan daya saing bagi Usaha Mikro Kecil dan Menengah (UKM) merupakan salah satu faktor yang perlu diperhitungkan. Hal tersebut berkaitan dengan peran UKM dalam pertumbuhan ekonomi nasional melalui terciptanya produk domestik bruto sebagai kontribusi nyata dari sektor tersebut sehingga menjadi nilai tambah secara nasional. Dengan adanya strategi peningkatan daya saing bagi UKM, maka peran UKM bagi sektor pembangunan perekonomian nasional akan semakin besar. Salah satu faktor yang cukup berperan penting untuk meningkatkan daya saing UKM adalah dengan mengadopsi teknologi informasi. Daya saing UKM dapat diwujudkan salah satunya dengan penggunaan Teknologi Informasi untuk